2005
DOI: 10.1637/7293-102604r
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Virulence-Associated Genes in Avian Pathogenic Escherichia coli by Multiplex Polymerase Chain Reaction

Abstract: Based on recently published prevalence data of virulence-associated factors in avian pathogenic Escherichia coli (APEC) and their roles in the pathogenesis of colibacillosis, we developed a multiplex polymerase chain reaction (PCR) as a molecular tool supplementing current diagnostic schemes that mainly rely on serological examination of strains isolated from diseased birds. Multiple isolates of E. coli from clinical cases of colibacillosis known to possess different combinations of eight genes were used as so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
2
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 33 publications
5
148
2
7
Order By: Relevance
“…List of primers used for detection of the virulence genes, and antibiotic resistance genes are shown in Table 1 (4,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Table 2 presents PCR conditions.…”
Section: Detection Of Upec Virulence Factors and Antibiotic Resistancmentioning
confidence: 99%
“…List of primers used for detection of the virulence genes, and antibiotic resistance genes are shown in Table 1 (4,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Table 2 presents PCR conditions.…”
Section: Detection Of Upec Virulence Factors and Antibiotic Resistancmentioning
confidence: 99%
“…Some of these traits are encoded chromosomally (11,15): fimC and papC responsible for adhesion factors F1 and P fimbriae, respectively, irp2 and fyuA for iron uptake systems, astA and vat for heat-stable toxin and vacuolating autotransporter toxin, respectively (7). Others are encoded in a plasmid termed "ColV plasmid" (12,20): colV for colicin V production, iss implicated in increased serum survival, tsh encoding temperature-sensitive hemagglutinin, and iucD encoding aerobactin secretions.…”
mentioning
confidence: 99%
“…Recent genetic approaches have suggested that a single or combination of these genes is prevalent in APEC. For instance, Dozois et al (5) suggested that tsh contributes most to APCE pathogenicity in the early stages of infection, whereas Ewers et al (6,7) reported that some virulence genes, especially fimC, fyuA, irp2, iss, and iucD are highly prevalent in APEC strains. Most recently, Johnson et al (12) claimed that a region of the ColV plasmid including iss and tsh is highly prevalent among APEC.…”
mentioning
confidence: 99%
“…Two strains, G12 and G13, possessed four or more virulence genes and therefore are considered APEC (Figure 3). G13 had the highly pathogenic phenotype containing iuc, iss is not well understood 13,12,20 The prevalence of the papC gene, which encodes for P fimbriae, may vary largely among APEC isolates, but it is very common in human uropathogenic E.…”
Section: Discussionmentioning
confidence: 99%